Data Compression: The Complete Reference - Salomon, David (Springer Verlag London Limited, 2007)
"This book provides a comprehensive reference for the many different types and methods of compression. Included are a detailed and helpful taxonomy, analysis of most common methods, and discussions on the use and comparative benefits of methods and description of ""how to"" use them. Detailed descriptions and explanations of the most well-known and frequently used compression methods are covered in a self-contained fashion, with an accessible style and technical level for specialists and nonspecialists. This 4th edition of this successful volume contains significant additional material as there has been tremendous progress in this field, especially in audio compression such as FLAC, AAC, WavPack, ALS and Dolby AC3, which are all covered. Additional key features include: RAR, Tunstall code, Differential and Hyperspectral Compression, LZMA, H.264, 3D data sets, PDF. This book provides an invaluable reference and guide for all researchers and practitioners needing a comprehensive compilation for a broad range of compression methods."